p53 promotes VEGF expression and angiogenesis in the absence of an intact p21-Rb pathway - Farhang Ghahremani, M (Nature Publishing Group, 2013)
There is growing evidence that the p53 tumour suppressor downregulates vascular endothelial growth factor (VEGF) expression, although the underlying mechanisms remain unclear and controversial. Here we provide insights from in vitro experiments and in vivo xenotransplantation assays that highlight a dual role for p53 in regulating VEGF during hypoxia. Unexpectedly, and for the first time, we demonstrate that p53 rapidly induces VEGF transcription upon hypoxia exposure by binding, in an HIF-1α-dependent manner, to a highly conserved and functional p53-binding site within the VEGF promoter. However, during sustained hypoxia, p53 indirectly downregulates VEGF expression via the retinoblastoma (Rb) pathway in a p21-dependent manner, which is distinct from its role in cell-cycle regulation. Our findings have important implications for cancer therapy, especially for tumours that harbour wild-type TP53 and a dysfunctional Rb pathway.